PENATAAN REGULASI LEMBAGA NEGARA MANDIRI DALAM STRUKTUR SISTEM KETATANEGARAAN INDONESIA - Ambarwati, Herika; Artina, Dessy; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The establishment of an independent state institution has different names, making it unclear in its accountability, through the third amendment to the 1945 Constitution of the Republic of Indonesia it was agreed that the formation of a Judicial Commission based on Article 24B Judicial Commission is independent, this does not give meaningful meaning to its institutional status , The Judicial Commission is clearly closer to the function of judicial power, because the Judicial Commission (KY) regulation is in the 1945 Constitution of the Republic of Indonesia (UUD NRI). In addition, there are also institutions that are at the same level as the Judicial Commission, namely state institutions. independent which has the same level of function. Unlike the Judicial Commission, these three institutions are not regulated in the constitution, namely the Attorney General's Office, the Corruption Eradication Commission, and the National Human Rights Commission. However, the regulation stipulated by article 24 paragraph (3) which states "Other bodies whose functions are related to judicial power are regulated in law" So that becomes a problem. This raises a big question why only the Judicial Commission is regulated in the Constitution?This research uses a typology of normative legal research or what is also called doctrinal legal research, which deals more specifically with legal principles. In this study the authors use descriptive research characteristics, because the authors describe the Regulatory Arrangement of Independent State Institutions in the Structure of the Indonesian State Administration System.The result of the research conducted by the author is that there must be regulation arrangement in an effort to equal position by regulating these independent state institutions including the Attorney General's Office, Komnas Ham, and the Corruption Eradication Commission in the Constitution. Structuring the regulations of independent state institutions is to make constitutional changes that reflect the position of institutions, especially independent institutions in the state administration structure in Indonesia. exercise of authority.Keywords: Regulatory, Structuring, Independent, State Institutions